(untitled) (International Research in Economics and Finance, 2022)
In the preceding 20 years, CSR reporting has made significant strides. This study examines the quality of CSR disclosure from the perspective of CSR restatements after reviewing prior literature. Long-term improvement in enterprises‟ quality of CSR disclosure is believed to be made possible by more advanced reporting requirements, improved services from skilled auditors, and continuously evolving CSR reporting systems.